Doctrina in Public International Law - Piotr LASKI (Communications of International Proceedings, 2021)
Doctrina, being sui generis a source of international public law, pursuant to the content of Article 38 of the ICJ Statute, provides an auxiliary source of adjudication and advisory opinions, which is to serve the Court in defining provisions of the law. Regardless of how this role has changed over the centuries, it still affects the process of creating international law, allowing for various spheres to be systematized and at the same time for its nature and the process of creation of international law norms to be explained
Keywords: Doctrina; Legal Norm; Judicial Decisions; Judiciary; Source Of Law